The effect of platelet-rich concentrates on orthodontic tooth movement: A review of randomized controlled trials. Issue 9 (September 2022) - Yao, Ke; Wu, Yongzhi; Cai, Jingyi; Wang, Yigan; Shen, Yu; Jing, Dian; Zhao, Zhihe
Abstract: Objectives: Platelet-rich concentrates, namely platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), have recently shown potential roles in accelerating orthodontic tooth movement (OTM) and reducing treatment duration. Our study aims to systematically evaluate the effect of platelet-rich concentrates on OTM. Materials and methods: An electronic search of 11 databases, followed by a hand search of reference lists of eligible studies and related reviews, was conducted up to January 2022. Randomized controlled trials investigating OTM of patients with platelet-rich concentrates were included. Risk of bias was assessed by version 2 of Cochrane tool (RoB 2) for assessing risk of bias in randomized trials. Results: Among 715 records initially identified, 9 studies were included, of which 3 used PRP and the other 6 applied PRF. 7 studies supported a positive relationship between platelet-rich concentrates and OTM, but the other 2 studies reported a null and a negative effect of PRF, respectively. The overall qualities of evidence were moderate to high. Conclusions: Platelet-rich concentrates as PRP and PRF seem to be effective in accelerating OTM at early stages, while their long-term efficacy remains controversial. Repeated application of platelet concentrates may increase the accelerated stability of OTM. Abstract : Orthodontic treatment; Platelet-rich plasma; Platelet-rich fibrin; Tooth movement.